Implementation The Altman Method (Z"-Scored) For Predicting Bankruptcy: Empirical study on Nondurable Household Products Subsector Companies Listed on Indonesia Stock Exchange in 2016-2022 - Indalesari, Rezki; Kurniaty; Zulfikar, Rizka; Yulianti, Farida; Lamsah (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This research was conducted to find out how many companies are included in the safe zone, grey zone, and danger zone. This study uses variables X1 to X4, namely X1 describes the ratio of working capital, X2 and X3 describes the ratio of operating profit and X4 describes the ratio which measures a company's ability to pay debts. The research design is a quantitative descriptive and an empirical study. The research population is all non-durable household products sub-sector companies listed on the Indonesia Stock Exchange in 2016-2022. The research sample was taken using purposive sampling, namely taking samples from the population based on certain criteria, and the number of samples was 5 companies for the 2016-2022 period. The results of this study indicate (1) Four of the five sample companies in this study are classified as not bankrupt, namely PT Mandom Indonesia Tbk, PT Mustika Ratu Tbk, PT Kino Indonesia Tbk and PT Unilever Indonesia Tbk. One company out of five samples is in the bankrupt category, namely PT Martina Berto Tbk. (2) The ratio of X1, X2, X3 and X4 with fluctuating values can cause the Z-Scored to fluctuate too.